ON THE APPLICABILITY OF THE PHASE SCANNING METHOD IN ANTENNA ARRAYS OF CHIRP PULSE RADARS - Galushko, V. G.; Vavriv, D. M. (Видавничий дім «Академперіодика», 2019)
PACS numbers: 84.40.Xb, 84.40.BaPurpose: Investigation of the space-and-time structure of the output signal of the antenna array (AA) of a chirp pulse radar in dependence on the frequency deviation range of the probe signal and analysis of the applicability condition for the phase scanning method in such systems.Design/methodology/approach: To calculate the space-and-time directional pattern (STDP) of the AA of a chirp pulse radar, the standard methods of mathematical physics and computer modeling are used.Findings: Formulas have been derived for calculating the output signal of the AA of a chirp pulse radar after optimum filtering in the case of beamforming using phase shifters and/or time-delay lines. An analysis has been made of distortions of the STDP pertaining to the phase scanning method in dependence on the frequency deviation range of the probe chirp signal with a fixed scanning angle, as well as of a function of the scanning angle with the frequency deviation range being fixed. An explanation has been suggested to the cause of arising of such distortion, and it has been shown that they are similar to the effects observed in the case of using taper windows for sidelobe suppression in the time and space (angular) domains. Based on the results obtained, an applicability condition has been formulated for the phase scanning in AAs of chirp pulse radars. It has been shown that minor violations of this condition result in decreasing the amplitude and broadening of the main lobe and sidelobes of the STDP of AAs. In the case of strong violations of the applicability condition for the phase scanning the sidelobes of the angular directional pattern degenerate merging with the main one into a single quite broad maximum. The effects considered lead to deterioration of the range and azimuth resolution capabilities of radars and should be taken into account when selecting the taper window parameters.Conclusions: The results obtained in this study should be taken into account when analyzing the range and angular resolution capability of chirp pulse radars made on the basis of AAs. To extend the tolerable frequency deviation range Δf  of the sounding signal for a specified angular scanning sector (or to enhance the scanning sector with a specified Δf), a hybrid method of AA beamforming can be used with application of both phase shifters (within subsections) and time-delay lines (for the subsection output signals).Key words: antenna array, directional pattern, phase scanning, chirp-pulse, pulse compression filterManuscript submitted 12.11.2019Radio phys. radio astron. 2019, 24(4): 285-299REFERENCES1. Foster, R. M., 1926. Directive diagrams of antenna arrays. Bell Syst. Tech. J. vol. 5, is. 2, pp. 292–307. DOI: https://doi.org/10.1002/j.1538-7305.1926.tb04302.x2. Hansen, R. C., 2009. Phased Array Antennas. Hoboken, New Jersey: John Wiley & Sons, Inc. DOI: https://doi.org/10.1002/97804705291883. Svetlov, A. V., 2017. Radiolocation: origin and development. Engineering and technology [online]. vol. 2, no. 1. (in Russian) DOI: https://doi.org/10.21685/2587-7704-2017-2-1-14. De Size, L. K. and Ramsay, J. F., 1964. Reflecting systems. Chapter 2. In: R. C. HANSEN, ed. Microwave scanning antennas. Vol. 1. Apertures. New York, London: Academic Press, pp. 107–213. DOI: https://doi.org/10.1016/B978-0-12-323901-3.50009-75. Cooley, M. E. and Davis, D., 2008. Reflector antennas. In: M. I. SKOLNIK, ed. Radar Handbook. New York, Chicago, San Francisco et al.: McGraw-Hill Companies, pp. 12.1–12.43.6. KUZ’MIN, S. Z., 2000. Digital radiolocation. Introduction to the theory. Kyiv, Ukraine: “KVITS” Publ. (in Russian).7. BCC RESEARCH, 2018. 5 Key Trends in Radar Technology. Radar Manufacturing: Global Markets to 2022. BCC Research Report IAS052A [online]. [viewed 15.10.2019]. Available from: http://blog.bccresearch.com/5-key-trends-in-radar-technology8. Frank, J. and Richards, J. D., 2008. Phased array radar antennas. In: M. I. SKOLNIK, ed. Radar Handbook. New York, Chicago, San Francisco et al.: McGraw-Hill Companies, pp. 13.1–13.74.9. Liu, M., Zou, L. and Wang, X., 2019. Practical Beamforming Technologies for Wideband Digital Array Radar. Prog. Electromagn. Res. Lett. vol. 86, pp. 145–151. DOI: https://doi.org/10.2528/PIERL1907230310. Jun, W., Duo-Duo, C. and Fan, Y., 2012. Aperture Effect Influence and Analysis of Wideband Phased Array Radar. Procedia Eng. vol. 29, pp. 1298–1303. DOI: https://doi.org/10.1016/j.proeng.2012.01.13011. Ajioka, J. S., 1993. Frequency scan antennas. Chapter 19. In: R. C. JOHNSON, ed. Antenna Engineering Handbook. New York, Louis, San Francisco et al.: Mc-Graw Hill, Inc., pp. 19.1–19.30.12. Mailloux, R. J., 2005. Phased Array Antenna Handbook. Boston, London: Artech House, Inc.13. Ducoff, M. R. and Tietjen, B. W., 2008. Pulse Compression Radar. In: M. I. SKOLNIK, ed. Radar Handbook. New York, Chicago, San Francisco et al.: McGraw-Hill Companies, pp. 8.1–8.44.14. MARTYNENKO, V. S., 1990. Operational calculus. Kyiv, Ukraine: Vyshcha shkola Publ. (in Russian).15. LEVIN, B. R., 1969. Theoretical fundamentals of statistical radio engineering. Part 1. Moscow, USSR: Sovetskoe radio Publ. (in Russian).16. Cook, C. E. and Bernfeld, M., 1967. Radar Signals: An Introduction to Theory and Application. New York, London: Academic Press.17. Doerry, A. W., 2017. Catalog of Window Taper Functions for Sidelobe Control. Technical Report SAND2017-4042, Sandia National Labs., Albuquerque, New Mexico and Livermore, California, USA. DOI: 10.2172/1365510 [viewed 15 October 2019]. Available from: https://prod-ng.sandia.gov/techlib-noauth/access-control.cgi/2017/174042.pdf